Back to Paul Revere! : Travelers Through Time #2 - Beatrice Gormley (New York, NY : Scholastic, Inc., 1994)
Matt and Emily's grandfather has invented a way to travel back in time. Now Matt, Emily, and Matt's best friend Jonathan are about to take a trip to the night the American Revolution began. They arrive in Lexington, Massachusetts, in the year 1775 just in time to see Paul Revere ride by, warning the country that the Redcoats are coming. Then they get separated. Matt is captured by the British and discovers that Paul Revere has been captured, too. Emily makes a wild cross-country horseback ride of her own. And Jonathan finds himself in the middle of a famous battle!
"An Apple paperback."
Keywords: Revere, Paul; Historical Fiction -- Historical Fiction